The RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND COMPLEMENTARY FEEDING WITH TODDLER GROWTH IN PAUD AN-NUR SUB-DISTRICT BLUE-BIRU DELI SERDANG DISTRICT - Samura, M Dasril (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
The growth and development of infants are primarily influenced by the nutrients found in breast milk, which include proteins, carbohydrates, minerals, and vitamins essential for their health and growth. As toddlers reach 6-24 months old, their energy requirements increase, necessitating additional nutritional support through appropriate complementary feeding (MP-ASI) to foster optimal growth and development. The objective of this study was to explore the correlation between exclusive breastfeeding and MP-ASI practices with toddler growth and development at An-Nur Paud, Biru-Biru District, Deli Serdang Regency. This research adopted a cross-sectional design, encompassing the entire population as its sample. Thirty-two mothers and toddlers aged between three and five years participated as respondents. Data collection employed questionnaires on exclusive breastfeeding and MP-ASI, alongside z-score charts. Statistical analysis utilized the chi-square test. Findings indicate a significant association between exclusive breastfeeding and toddler growth (p-value = 0.001, <0.05), as well as between complementary feeding and toddler growth (p-value = 0.000, <0.05). Consequently, this study concludes that there exists a correlation between exclusive breastfeeding and MP-ASI practices with the growth and development of toddlers at Paud An-Nur, Biru-Biru District, Deli Serdang Regency in 2024. It is hoped that these findings will encourage mothers to prioritize exclusive breastfeeding and MP-ASI practices based on this research.